Pengembangan Garis Lapangan Portabel Berbahan Kulit Kayu Kapuak untuk Pembelajaran Pendidikan Jasmani Materi Bulu Tangkis : Development of Portable Court Lines Made of Kapuak Bark for Physical Education Learning in Badminton Material - Fitri Fitri; Dwi Qomara; Yulita Yulita (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2026)
This study aims to develop a portable court line made from kapuak bark as a learning medium for physical education in badminton at MIS Istiqomah Entikong and SDN 20 Mabah in the border area of Sanggau Regency, West Kalimantan. The method used is Research and Development (R&D), with the ADDIE model limited to three stages (Analyze, Design, Develop), because this study focuses on the development and assessment of prototype feasibility rather than measuring learning effectiveness. One physical education expert assessed product feasibility, one badminton court expert, and two PJOK teachers, who served as user respondents. Data analysis used the Percentage of Agreement formula (Grinnell, 1988). The results showed validation by physical education experts at 100% (Very High), by field experts at 60% (Moderate), and by PJOK teachers at 100% (Very High). The 60% score from field experts indicates that the product has not met the technical feasibility threshold and requires substantial revisions to material durability, line stability, and dimensional conformity with BWF standards. Further research with more validators and measurement of the impact on student learning outcomes is needed.